Tubulin, actin and heterotrimeric G proteins: Coordination of signaling and structure - Schappi, Jeffrey M.; Krbanjevic, Aleksandar; Rasenick, Mark M. (Biochimica et biophysica acta, 2014)
G proteins mediate signals from membrane G protein coupled receptors to the cell interior, evoking significant regulation of cell physiology. The cytoskeleton contributes to cell morphology, motility, division, and transport functions. This review will discuss the interplay between heterotrimeric G protein signaling and elements of the cytoskeleton. Also described and discussed will be the interplay between tubulin and G proteins that results in atypical modulation of signaling pathways and cytoskeletal dynamics. This will be extended to describe how tubulin and G proteins act in concert to influence various aspects of cellular behavior. This article is part of a Special Issue entitled: Reciprocal influences between cell cytoskeleton and membrane channels, receptors and transporters.This article is part of a Special Issue entitled: Reciprocal influences between cell cytoskeleton and membrane channels, receptors and transporters. Guest Editor: Jean Claude Hervé. [Display omitted] •Tubulin promotes receptor-independent activation of G proteins.•Heterotrimeric G proteins promote tubulin GTPase, increasing microtubule dynamics.•GPCR activation releases Gα and Gβγ from plasma membrane, modifying cell morphology.